Konflik Pengawas Dengan Kepala Sekolah Dalam Pelaksanaan Supervisi Manajerial Di Kota Pekanbaru - Said Suhil Achmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
Principals in performing their duties will receive supervision from supervisors,particularly in the managerial aspects, but its implementation is expected to be conflict, because noteveryone is able to work with a bunch of good, especially the organizational structure in which certainpeople are worth it or not placed there it would trigger conflict, high conflict How did that happen?How high intensity. This is the assessment in this study, namely to determine the level of conflictbetween the principal and superintendent with the level of intensity due to the conflict between thesuperintendent to the principal; relationship between the level of conflict with supervisors conflict; withthe principal, and superintendent for the differences in the level of conflict the principal factors gender,education level, and years of supervisor. This study classified descriptive study, carried out inaccordance with the stage of the research is to test instruments, data collection, and data analysis. Datacollection using the questionnaire in the form of a Likert scale, while data analysis is done using themethod with the help of SPSS Statistics version 17. The population of this research is all the schoolsuperintendent in the city of Pekanbaru as many as 96 people. Sampling using